2020
DOI: 10.3390/microorganisms8101615
|View full text |Cite
|
Sign up to set email alerts
|

Human mecC-Carrying MRSA: Clinical Implications and Risk Factors

Abstract: A new methicillin resistance gene, named mecC, was first described in 2011 in both humans and animals. Since then, this gene has been detected in different production and free-living animals and as an agent causing infections in some humans. The possible impact that these isolates can have in clinical settings remains unknown. The current available information about mecC-carrying methicillin resistant S. aureus (MRSA) isolates obtained from human samples was analyzed in order to establish its possible clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 97 publications
1
33
0
Order By: Relevance
“…But also here, bacteria emerge that have acquired resistance to these antibiotics through mutations in pbp2 , pbp4 and gdpP 11 . Another cause of β-lactam resistance is the expression of mecC that encodes for a PBP2a/2′ variant 12 .…”
Section: Introductionmentioning
confidence: 99%
“…But also here, bacteria emerge that have acquired resistance to these antibiotics through mutations in pbp2 , pbp4 and gdpP 11 . Another cause of β-lactam resistance is the expression of mecC that encodes for a PBP2a/2′ variant 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, this lineage has been detected in diverse hosts in many European countries, with cattle and wildlife (including free grazing domesticated animals) being the most common hosts ( Zarazaga et al, 2018 ). The prevalence of mecC -MRSA in people seems to be low ( Paterson et al, 2014a , b ; Lozano et al, 2020 ), however, the zoonotic transmission from livestock to people has been reported ( Harrison et al, 2013 ), as well as its ability to cause disease ( Petersen et al, 2013 ). This mecC -MRSA-CC130 lineage seems to be susceptible to many non-β-lactam agents and lacks major human virulence factors ( Cuny et al, 2011 ; Monecke et al, 2013 ; Paterson et al, 2014a ).…”
Section: Introductionmentioning
confidence: 99%
“…This IEC system is found in seven different configurations (types A–G) depending on the combination of five genes ( scn , chp , sak , sea / sep ); the scn gene (encodes a staphylococcal complement inhibitor) is included in all IEC types, and is often used as a marker of IEC-positive isolates, and is functionally essential ( van Wamel et al, 2006 ). None of the mecC -MRSA reported strains harbored the scn gene (essential for the IEC system) ( Lozano et al, 2020 ), with the exception of a few isolates belonging to ST1945, ST1581, and ST1583 previously described by our group from wildlife and extensively farmed domestic animals ( Gómez et al, 2014 , 2015 ; Ruiz-Ripa et al, 2019 ) and one ST1945 MRSA strain from a human sample ( Harrison et al, 2017 ); it is worth noting that all these IEC-positive isolates were of type-E (carrying the scn and sak genes).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon implies a diminishing existence of effective antimicrobial agents to treat infections caused by these bacteria (Magiorakos et al, 2012;Lin et al, 2017). Among antibiotic-resistant bacteria, methicillin-resistant Staphylococcus aureus (MRSA) is spreading worldwide in both hospital (HA-MRSA) and community (CA-MRSA) settings, including livestock animals (LA-MRSA) (Castro et al, 2017;Lakhundi & Zhang, 2018;Lozano et al, 2020;Togneri et al, 2017). Infections caused by MRSA constitute one of three major infectious diseases, threatening human health (Center for Disease Control and Prevention, 2015;Lozano et al, 2020;Togneri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%